Barriers to the Use of Trastuzumab for HER2+ Breast Cancer and the Potential Impact of Biosimilars: A Physician Survey in the United States and Emerging Markets - Philip Lammers; Carmen Criscitiello; Giuseppe Curigliano; Ira Jacobs (MDPI AG, 2014)
Trastuzumab in combination with chemotherapy has become a standard of care for patients with HER2+ breast cancer. The cost of therapy, however, can limit patient access to trastuzumab in areas with limited financial resources for treatment reimbursement. This study examined access to trastuzumab and identified potential barriers to its use in the United States, Mexico, Turkey, Russia and Brazil via physician survey. The study also investigated if the availability of a biosimilar to trastuzumab would improve access to and use of HER2 monoclonal antibody therapy. Across all countries, a subset of oncologists reported barriers to the use of trastuzumab in a neoadjuvant, adjuvant or metastatic setting. Common barriers to the use of trastuzumab included issues related to insurance coverage, drug availability and cost to the patient. Overall, nearly half of oncologists reported that they would increase the use of HER2 monoclonal antibody therapy across all treatment settings if a lower cost biosimilar to trastuzumab were available. We conclude that the introduction of a biosimilar to trastuzumab may alleviate cost-related barriers to treatment and could increase patient access to HER2-directed therapy in all countries examined.